Prior use-dependent plasticity triggers different individual corticomotor responses during persistent musculoskeletal pain - Zamorano, Anna; Kleber, Boris; De Martino, Enrico; Insausti-Delgado, Ainhoa; Vuust, Peter; Flor, Herta; Graven-Nielsen, Thomas (Pain, 2025)
Movement repetition is crucial for pain interventions. It facilitates the rehabilitation of motor patterns, the acquisition of motor skills, and the genesis of adaptive use-dependent plasticity. However, the influence of prior motor experience and preexisting use-dependent plasticity on pain severity and progression remains poorly investigated. This study investigated the effects of preexisting use-dependent plasticity during the development of prolonged experimental musculoskeletal pain. Using transcranial magnetic stimulation, corticospinal excitability was assessed by measuring the Rest motor threshold (RMT), motor-evoked potential (MEP), representational area of the motor map, volume, and center of gravity of the first dorsal interosseous (FDI) muscle in musicians (n = 19), a well-known ecological model of use-dependent plasticity, and in nonmusicians (n = 20). All participants attended 3 sessions (day 1, day 3, day 8). Prolonged pain for several days was induced by intramuscular injection of nerve growth factor (NGF) into the right FDI muscle at the end of day 1. Compared to day 1, prolonged pain uniquely led to reduced motor map volume in nonmusicians on day 3 (P = 0.004), who also showed higher NGF-related pain intensity compared to musicians. The motor maps of musicians, which were already smaller in pain-free conditions (day 1) compared to nonmusicians (P = 0.021), remained nonsignificantly different across days. Notably, corticomotor responses (map volume, MEP amplitude, and RMT) were correlated to weekly and accumulated musical training. These findings demonstrate that preexisting use-dependent plasticity associated with motor training may counteract the effects of prolonged pain in the motor system. Moreover, it confirms that prior motor experience acts as a source of individual variability to pain.